Students’ Perception on the Use of WhatsApp Messenger as a Learning Tool in Writing Class - Dhizella Fasha Salwa Salsabella (English Education Department Slamet Riyadi University Surakarta, 2020)
This research was concerned with the students' perception of the use of Whatsapp in teaching writing. The objectives of this research were as follows: 1) to analyze the activities were carried out in using WhatsApp messenger in the learning process at the Seventh Grade Students of SMP N 18 Surakarta in Academic Year 2019/2020; 2)To analyze the students perceive the applications and students’ perception towards the use of WhatsApp at the Seventh Grade Students of SMP N 18 Surakarta in Academic Year 2019/2020; 3)to analyze students frequency in use WhatsApp Messenger to learn writing skills the Seventh Grade Students of SMP N 18 Surakarta in Academic Year 2019/2020. In this research, the researcher used qualitative method. The researcher used source observation, interview, questionnaire, and documents as the source of the data. The result of this research showed that there were some activities were carried out using WhatsApp such as: the students used WhatsApp as the tool for communication and discussion with their friend or the teacher outside the class, sent the assignment by students, giving assignment by teacher. The students perception toward using WhatsApp such as: students can learn anywhere and save their energy in learning English, WhatsApp help students to develop their English writing. The students frequency in using WhatsApp such as: students used WhatsApp to did their assignment and sent the result to the teacher at least once a week, students used WhatsApp to communicate with their friends everyday. Keywords:Writing Skills,Whatsapp Messenger,ICT,Whatsapp for Teaching Writing.